Генеза топонімів доби Кримської війни 1853–1856 рр. у лексичній системі англійської мови - Рибакова, Катерина Анатоліївна; Rubakova, K. A. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено генезу 419 топонімів доби Кримської війни 18531856 рр. як складників лексичної системи англійської мови. Встановлено, що у результаті свого розвитку запозичені топоніми, джерелами яких є тюркська, грецька та російська мови, асимілювались до структури англійської мови. Виявлено різноманітні типи англомовних топонімів кримського походження, які функціонують у різних угрупованнях, представлених низкою структурних моделей. Виявлено найбільш продуктивну та найпоширенішу складну двокомпонентну модель, яка складається із власного іменника та топонімотворчого іменника в однині. Проаналізовано, що за типом геогра¬фічних об’єктів кримські топоніми класифікуються як астроніми, геоніми, гідроніми, годроніми, дромоніми, мікротопоніми, ойконіми та урбоніми. This article focuses on the rise and the origin of 419 toponyms borrowed to the lexical system of the English language during the Crimean War period (1853–1856). The paper examines the borrowed onomastic elements that etymologicaly belong to the Turkish, Greek and Russian languages and had assimilated into the structure of the English language. It outlines the different types of English place-names and street-names of the Crimean origin that belong to different groups and are represented by a number of structural patterns. The paper identifies the most frequent and productive two-component complex pattern that consists of a personal noun and generic common noun in the singular. The article concludes in suggesting a classification of the assimilated Crimean toponyms according to their generic elements and illustrates that generic names of the borrowed place-names include hydronyms, microtoponyms, street-names, road-names, names of the settlements, farms, villages and towns.
The Rise and the Origin of Toponyms Borrowed to the Lexical System of the English Language During the Crimean War Period
Keywords: топоніми; toponymy; запозичена лексика borrowed; vocabulary; етимологія; etymology